2017
DOI: 10.1080/17461391.2017.1308560
|View full text |Cite
|
Sign up to set email alerts
|

Side‐to‐side differences in lower extremity biomechanics during multi‐directional jump landing in volleyball athletes

Abstract: Side-to-side differences of lower extremities may influence the likelihood of injury. Moreover, adding the complexity of jump-landing direction would help to explain lower extremity control during sport activities. The aim was to determine the effects of limb dominance and jump-landing direction on lower extremity biomechanics. Nineteen female volleyball athletes participated. Both dominant limbs (DLs) and non-dominant limbs (NLs) were examined in single-leg jump-landing tests in four directions, including for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 48 publications
5
23
0
Order By: Relevance
“…Another interesting finding in this study is that the structure of the patellar tendon in the dominant side behaved differently than the non‐dominant side—possibly because tendon structure may be influenced not only by jump frequency but also by the biomechanics involved. For example, during landing the knee is in external rotation on the non‐dominant side and in internal rotation on the dominant side . This is in line with our results that show a significant relation between load and changes in tendon structure on the dominant side—which as a result of these different biomechanical features of landing may explain the dominant/non‐dominant variation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another interesting finding in this study is that the structure of the patellar tendon in the dominant side behaved differently than the non‐dominant side—possibly because tendon structure may be influenced not only by jump frequency but also by the biomechanics involved. For example, during landing the knee is in external rotation on the non‐dominant side and in internal rotation on the dominant side . This is in line with our results that show a significant relation between load and changes in tendon structure on the dominant side—which as a result of these different biomechanical features of landing may explain the dominant/non‐dominant variation.…”
Section: Discussionsupporting
confidence: 90%
“…For example, during landing the knee is in external rotation on the non-dominant side and in internal rotation on the dominant side. 35 This is in line with our results that show a significant relation between load F I G U R E 4 Echo type percentages over the 7-week preseason and changes in tendon structure on the dominant side-which as a result of these different biomechanical features of landing may explain the dominant/non-dominant variation. This is the first study to investigate the relation between load (weekly) and changes in patellar tendon structure (biweekly) of male elite volleyball players.…”
Section: Weekly Jump Frequency (Jumps)supporting
confidence: 91%
“…This supports the use of unilateral jump-landing test as an appropriate assessment of the risk of lower extremity landing injuries (Sinsurin et al, 2013;Sinsurin et al, 2017;Tamura, Akasaka, Otsudo, Schiozawa, Toda, & Yamada, 2017). Therefore, this study examined jump-landing test with one leg.…”
Section: Jump-landing Testsmentioning
confidence: 72%
“…Previous studies (Sinsurin et al, 2013;Sinsurin et al, 2017) exhibited that lateral jump landing needed higher knee flexion at initial contact than forward and diagonal directions. They suggested that lateral jump landing has the higher risk of knee injury compared to forward and diagonal directions.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation